Estrategias pedagógicas para la mejora del rendimiento académico en los estudiantes de primer año de bachillerato de la unidad educativa Juan Montalvo, cantón Buena Fe; periodo 2021-2022. - Rodríguez Sánchez , Sandra Patricia (2021)
Through this research, the effect of pedagogical strategies on academic performance was analyzed, taking as an object of study the Juan Montalvo Educational Unit, located in the San Jacinto de Buena Fe canton, Los Ríos Province. The diagnosis, exploration and approach of the proposal included as a sample the administrative staff (2), teachers of the social sciences area (11) and students of the first year of high school (270), to whom the survey was applied as a technique and the questionnaire as an instrument. According to the nature of the research, it has a quantitative approach, descriptive, purposeful, explanatory and documentary, contributing to the understanding of the study variables through the theoretical, conceptual and legal foundation. The objective of the study was to establish the evaluation of pedagogical strategies to improve the academic performance in the area of social sciences of the students of the first year of high school of the Juan Montalvo Educational Unit of the Buena Fe canton, period 2021-2022. From the general objective, the following specific objectives arise: to know the academic performance in the area of social sciences of the students of 1st of Baccalaureate, identify the factors that can affect the academic performance in the area of social sciences of the students, analyze the level of knowledge of the teachers' competence in pedagogical strategies and develop a teacher improvement plan in pedagogical strategies for the teachers of the Juan Montalvo Educational Unit. The research answered the question posed around the identified problem, explaining that pedagogical strategies influence the improvement of academic performance in the area of social sciences in students of the first year of high school of the Juan Montalvo educational unit of the Buena Fe canton in the period 2021-2022.